Keterampilan Komunikasi Juru Dakwah di Kelurahan Balai Gadang Kecamatan Koto Tangah Padang - Muhammad Al Hafizh; Desvalini Anwar (Universitas Negeri Padang, 2023)
The training of rhetoric techniques in the sub-district of Balai Gadang Padang is aimed at improving the communication skills of the Islamic preachers or ‘juru dakwa’h in delivering their sermon or ‘khutbah’. With the improved skills, it is expected that their audience will receive and understand the messages delivered to them more easily. Rhetoric tehcnique or also known as ‘the art of speaking’ is a special skill used to speak in front of a larger audience whose purpose is not only to enable the listeners to understand the messages but more importantly to persuade them to agree with the opinions or statements shared by the ‘juru dakwah’. This ‘art of speaking’ is the most crucial to master since it can determine the success or failure of ‘a khutbah’. It also highlights the uniqueness of the preacher. Three rhetoric techniques were taught during this public service training namely; 1) monologue rhetoric involving only one speaker such as those found in speeches, sermons and declamation, 2) dialogical rhetoric involving two or more speakers like in discussion, conversation, debates, and colsultation and 3) speaking techniques coaching involving training to practice breathing, resonating, projecting, articulating and storytelling.